2020
DOI: 10.18502/kss.v4i7.6838
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Computer Misuse in the Workplace

Abstract: Computer misuse leads to computer-related injuries. The incidence of computer-related injuries (CRIs) is reported having a high incidence among office personnel who works routinely with the computer. The purpose of this research is to figure out the incidence of computer-related injuries in an organization with a majority of employees using technology such as a computer. This research is a survey of 120 office personnel selected with a simple random sampling method. The data was collected by distributing a sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A study conducted by Kanchanomai et al, [23] revealed neck pain that persisted, including some aspects related to computer use. Computer use suffered musculoskeletal disorders such as neck, shoulder, and waist pain [24]. Moreover, computer use impacts healthy older people's daily functioning, well-being, and happiness, as well as their social network [25].…”
Section: Consequences Of Prolonged Using Personal Computermentioning
confidence: 99%
“…A study conducted by Kanchanomai et al, [23] revealed neck pain that persisted, including some aspects related to computer use. Computer use suffered musculoskeletal disorders such as neck, shoulder, and waist pain [24]. Moreover, computer use impacts healthy older people's daily functioning, well-being, and happiness, as well as their social network [25].…”
Section: Consequences Of Prolonged Using Personal Computermentioning
confidence: 99%
“…Various kinds of crimes and criminal acts currently involve information and communication technology [1] [2]. The widespread of computers and other digital devices usage without security can lead various parties to crimes [3]. Perpetrators of crimes can be subject to punishment based on the evidence [4].…”
Section: Introductionmentioning
confidence: 99%